Role of peroral cholangioscopy and pancreatoscopy in the diagnosis and treatment of biliary and pancreatic disease: past, present, and future - Gopakumar, Harishankar; Sharma, Neil R. (Frontiers in Gastroenterology, 2023)
Peroral cholangiopancreatoscopy was described as early as the 1950s. However, the small caliber of these ducts and the technological limitations in developing slender, maneuverable high-definition scopes posed a challenge. Per-oral cholangiopancreatoscopy has now rapidly evolved. What began as dual-operator mother-daughter cholangioscopy systems which were fragile and difficult to use, are now single-operator systems. The development of high-definition video cholangioscopes, along with improved flexibility and accessory technologies in recent years, has permitted single-operator, highquality endoluminal examination, and therapies of the biliary and pancreatic ducts. It is now an indispensable modality in the comprehensive diagnosis and definitive management of complex biliary and pancreatic conditions like indeterminate biliary strictures and difficult-to-remove biliary and pancreatic stones. With enhanced imaging capabilities and refined maneuverability of the latest generation of cholangioscopes, the role of cholangiopancreatoscopy is expanding with applications in advanced gall bladder drainage, accurate determination of tumor stage, cholangioscopy directed tumor ablation, and selective biliary cannulation. In this review, we detail the evolution of this technology, the various approaches to per-oral cholangiopancreatoscopy, and it's established and emerging diagnostic and therapeutic indications. Furthermore, we discuss the current limitations and potential future applications of cholangioscopy and pancreatoscopy in managing various biliary and pancreatic pathologies.